Enhancing financial risk managment in corporation – a case of some vietnam listed banks - THANG, TRAN DUC; HUY, DINH TRAN NGOC; HA, NGUYEN THI THU; TINH, DUONG THI; NGON, NGUYEN THI TUYEN (The journal of contemporary issues in business and government, 2021)
Saigon Hanoi bank (SHB) and Sacombank (STB) are two big listed banks who opened lots of branches and hold big market shares in Vietnam. This paper use quantitative and quantitative methods in order to estimate risks of these two banks and make comparison. Study findings show that market risk, beta CAPM of SHB bank higher than those of STB bank during pre-low (L) inflation stage, but lower during post low inflation time. Based on above results we can propose risk policies for banks, bank system, State bank and relevant agencies.